Rare bird documentation form for Tundra Swan at Pool 13, 1999 - Lesher, Fredet al (1999)
Rare bird documentation form for seventy or more Tundra Swans at Pool 13 in Clinton County, IA on December 16, 1999. Epson - sheet feed